REKONSTRUKSI PENGELOLAAN WAKAF: BELAJAR PENGELOLAAN WAKAF DARI BANGLADESH DAN MALAYSIA - Nilna Fauza (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2015)
Waqf is a unique Islamic economic instruments that bases its function on the elements of virtue (birr), goodness (ihsan) and fraternity (brotherhood). Therefore, in order endowments can be managed productively, it is proper we reconstruct the management of waqf in Indonesia to study and refl ect on the country or institution that has been able to manage endowments properly. This article examines the management of waqf of Bangladesh and Malaysia. Focussing assessments on critical thinking and innovative endowments management system, covering Operationalization of the Social Investment Bank Limited in Bangladesh, Operationalization Certifi cate Endowments Money, Cash Waqf in Malaysia. The systems offered by Bangladesh and Malaysia are the commercial-style systems. Such trends illustrate that the strengthening of the role of endowments in both countries have been reconstruction (an increase towards better), namely (1) from the traditional to the waqf endowments productive, (2) of the goods remains to move goods, in this case the cash endowments, and ( 3) from the beginning that only relies on traditional instruments which is taking a direct benefi t from the existing endowment, the endowment development efforts through commercial instruments. If Indonesian muslims are able to carry out that reconstruction on a large scale, it will show the positive implications of the activities of the cash endowments, cash endowments have unique opportunities for the creation of an investment in the fi elds of religion, education and social services.